1973
DOI: 10.1111/j.1440-1827.1973.tb02780.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURAL and HISTOCHEMICAL STUDIES OF VASCULAR LESIONS IN MARFAN'S SYNDROME, WITH REPORT OF 4 AUTOPSY CASES

Abstract: Histochemical observation was conducted on arterial lesion in 4 cases of Marfan's syndrome and electron microscopic observation was also carried out on the aorta and gastroepiploic artery in 2 of the 4 cases. Acid mucopolysaccharide (AMPS) noted In cystic medionecrosis demonstrated meshwork of spheres and threads, and showed the same structure as the ground substances widely distributed in the mesenchymal connective tissues including normal arteries and as AMPS in cystic medionecrosis‐like lesions such as arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Elastic fiber calcification, intimal hyperplasia, and abnormal deposition of matrix elements were observed widely in medium-to-large elastic arteries. Takebayashi et al 41,42 had previously reported an odd appearance of fragmented elastic laminae in the media of the aorta and peripheral arteries in patients with MFS. This "osmiophilic elastolysis" was characterized by the accumulation of an electron-dense and granular material on the surface of and within elastic fibers.…”
Section: Discussionmentioning
confidence: 97%
“…Elastic fiber calcification, intimal hyperplasia, and abnormal deposition of matrix elements were observed widely in medium-to-large elastic arteries. Takebayashi et al 41,42 had previously reported an odd appearance of fragmented elastic laminae in the media of the aorta and peripheral arteries in patients with MFS. This "osmiophilic elastolysis" was characterized by the accumulation of an electron-dense and granular material on the surface of and within elastic fibers.…”
Section: Discussionmentioning
confidence: 97%
“…The specific defect underlying the Marfan syndrome is not known, but the phenotypic manifestations and the autosomal dominant inheritance suggest that the defect results in abnormal structural protein( s) of connective tissue (McKusick, 1972; 'Address reprint requests to T. E. Besser, Department of Veterinary Microbiology and Pathology, Washington State University, Pullman, WA 99164-7040. Takebayashi et al, 1973;Saruk and Eisenstein, 1977). Patients with the Marfan syndrome characteristically exhibit joint laxity, thin limbs, arachnodactyly, ectopia lentis, and dilation of the aortic root leading eventually to dissecting aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…The histological and ultrastructural observations have indieated that the major pathologic feature of the vascular lesions in Marfan syndrome resides in the elastie tissues; fragmentation and sparsity of the elastic fibers, eracks and holes in their amorphous material, and formation of new elastin and non-banded microfibrils (12,(14)(15)(16)(17). The collagen fibers appeared normal (14-17), or twisted (12).…”
mentioning
confidence: 99%